Ultrastructural immunolocalization of cyclin/PCNA in synchronized 3T3 cells - Raska, I; Koberna, K; Jarník, M; Petrasovicová, V; Bednár, J; Raska, K; Bravo, R (Experimental cell research, 1989)
The immunolocalization of cyclin/PCNA in synchronized 3T3 cells was performed with human autoantibodies using an immunogold technique performed on thin cryosections. Previous immunofluorescent studies demonstrated that the DNA replication sites correspond to the localization of bound cyclin. We have found that in the early periods of S phase, the DNA replication sites (or sites potentially ready for the replication during the hydroxyurea DNA synthesis block) are situated in the perichromatin region and correspond to clustered gold particles present frequently over a morphologically distinct small nuclear area. Heavily labeled chromocenters, including perinucleolar condensed chromatin, exhibiting several such distinct areas were found in later periods of S phase.
Keywords: Cell Line; jaderné proteiny; buněčné jádro; proliferační antigen buněčného jádra; Nuclear Proteins; DNA Replication; imunohistochemie; replikace DNA; kompartmentace buňky; hydroxymočovina; Mice; Proliferating Cell Nuclear Antigen; Immunohistochemistry; Cell Nucleus; zvířata; Cell Compartmentation; myši; buněčné linie; Hydroxyurea; Animals